2020
DOI: 10.3926/jiem.3100
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical supply chain transformation through application of the Lean principle: A literature review

Abstract: Purpose: This study aims to review the previous literature on the topic contained in the title in order to identify gaps in the existing research relating to lean supply chain-related issues within the pharmaceutical industry since limited attention has been devoted to this sector.  Design/methodology/approach: This study presents a systematic literature review that proposes an analysis and classification of the previous literature as falling within one of four categories, namely; the supply chain area, resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Garza-Reyes et al (2019) used internet-based tools to improve communication and enhance the control of stretches, thus achieving better integration between the vehicles and the health-care provider. However, despite the evolution of the lean concept in the transportation sector (Argiyantari et al , 2020), this study found that prior studies have failed to examine the lean application’s effect on transportation in the pharmaceutical industry.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Garza-Reyes et al (2019) used internet-based tools to improve communication and enhance the control of stretches, thus achieving better integration between the vehicles and the health-care provider. However, despite the evolution of the lean concept in the transportation sector (Argiyantari et al , 2020), this study found that prior studies have failed to examine the lean application’s effect on transportation in the pharmaceutical industry.…”
Section: Resultsmentioning
confidence: 88%
“…Thus, studies dedicated to the pharmaceutical industry are needed (Alkhalidi and Abdallah, 2018). In line with the aforementioned statement, Argiyantari et al (2020) argued that specifically, research into the pharmaceutical industry enables to validate the findings that fit with industry characteristics.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Emvolio can not only fill the gap of the lack of technology access in the rural area, but also can help the healthcare workers to get accurate sample data with minimum damage. Pharma-logistics, as well as academia, have suffered from a lack of reliable last-mile transport 25 . So, technical support is required to aid the healthcare sector in coping with the storage and transportation facility of biologicals.…”
Section: Analytesmentioning
confidence: 99%